2005
DOI: 10.1111/j.1398-9995.2006.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

3‐Nitrotyrosine, a marker of nitrosative stress, is increased in breath condensate of allergic asthmatic children

Abstract: Nitrotyrosine is high in EBC of asthmatic children and could be considered as a noninvasive marker of nitrosative events in the airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 25 publications
2
47
1
Order By: Relevance
“…After a short course of oral steroids, MDA was reduced to levels similar to those detected in healthy children, while glutathione was increased but still lower than in healthy children [3]. In EBC of asthmatic children, we found increased levels of both 8-isoprostane [4], a product of the lipid peroxidation of arachidonic acid, and 3-nitrotyrosine [5], a product of the reaction between the potent oxidant peroxynitrate and a tyrosine residue. Although significantly higher in asthmatic than in healthy children, both these markers of oxidative stress were not different in children either treated or not treated with inhaled steroids [4,5].…”
Section: My Research As Part Of My Working Group/ Research Teamsupporting
confidence: 48%
“…After a short course of oral steroids, MDA was reduced to levels similar to those detected in healthy children, while glutathione was increased but still lower than in healthy children [3]. In EBC of asthmatic children, we found increased levels of both 8-isoprostane [4], a product of the lipid peroxidation of arachidonic acid, and 3-nitrotyrosine [5], a product of the reaction between the potent oxidant peroxynitrate and a tyrosine residue. Although significantly higher in asthmatic than in healthy children, both these markers of oxidative stress were not different in children either treated or not treated with inhaled steroids [4,5].…”
Section: My Research As Part Of My Working Group/ Research Teamsupporting
confidence: 48%
“…(21) Although nitrotyrosine and adenosine have also been studied, neither has been shown to be a gold standard marker. (22) It is possible that a "combination of markers" (6) is required in order to differentiate asthma In a study conducted in 2007, a new device was used-the same as that used in the present study-and was shown to be extremely easy to use. (9) The device dispenses with the use of mouthpieces, special sensors, and calculations to determine study points on the EBT increase curve.…”
Section: Discussionmentioning
confidence: 94%
“…Buss et al (2003) observed 3-chlorotyrosine in tracheal aspirate in significantly higher amounts in preterm infants with respiratory distress than in control infants. Nitrotyrosine was increased in exhaled breath condensate in patients with mild asthma (Hanazawa et al, 2000), in children (Baraldi et al, 2006) and in airway epithelial lining fluid of asthmatic children (Fitzpatrick et al 2009). …”
Section: Protein Oxidative Damagementioning
confidence: 96%